Pengaruh Transformasi Digital Dan Adaptasi Teknologi Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada Badan Pendapatan Daerah (BAPENDA) Pasaman Barat - Guspadli Ananda; Robby Dharma; Omia Crefioza (CV. ITTC INDONESIA, 2026)
This study aims to analyze the influence of Digital Transformation and Technology Adaptation on Employee Performance through Job Satisfaction as an intervening variable at the West Pasaman Regional Revenue Agency (Bapenda). The phenomenon underlying this study is the suboptimal achievement of employee performance targets, which impacts work productivity. This study uses a quantitative approach with data collection techniques through questionnaires and observations of 42 respondents. Data analysis was conducted using the SmartPLS 3.0 program with stages of validity testing, reliability testing, and hypothesis testing. The results show that Digital Transformation has a positive but insignificant effect on Job Satisfaction, while Technology Adaptation has a negative and insignificant effect on Job Satisfaction. Digital Transformation was also found to have a negative and insignificant effect on Employee Performance. Conversely, Technology Adaptation has a positive and significant effect on Employee Performance. In addition, Job Satisfaction is unable to mediate the influence of Digital Transformation or Technology Adaptation on Employee Performance. These findings indicate that the improvement of employee performance at the West Pasaman Bapenda is more influenced by the ability to adapt to technology than direct digital transformation, and the role of job satisfaction has not been an effective mediating factor. Therefore, efforts to improve technological competency and strengthen the implementation of digital transformation in a more targeted manner are needed to support sustainable employee performance improvements.